Allegations of misuse of African DNA in the UK: Will data protection legislation in South Africa be sufficient to prevent a recurrence?. Issue 3 (7th August 2020) - Moodley, Keymanthri; Kleinsmidt, Anita
Abstract: Concerns have been raised around the alleged commercialisation of South African genetic material by various research institutes nationally and abroad. We consider whether the Protection of Personal Information Act in South Africa will conflict with or complement existing protections in health law and research ethics. The Act is not applicable to de‐identified samples that cannot be re‐identified but we question whether genetic samples can ever be truly de‐identified. The research participants in this matter provided consent for use of their samples for research but did not consent to commercialisation by global research institutions, and neither did the researchers. We suggest that consent models incorporating broad consent as an option should include explicit discussions around benefit sharing and commercialisation. Mistrust between researchers and participants impedes scientific research and can harm relationships built up over the years between South African researchers and local communities.